Pengaruh Terapi Aktivitas Kelompok Stimulasi Sensori: Menggambar terhadap Perubahan Tingkat Halusinasi pada Pasien Halusiansi di Ruang Rawat Inap Rumah Sakit Jiwa Daerah Jambi - Kamariyah Kamariyah; Yuliana Yuliana (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Indonesia According to WHO (2017) data, there are about 35 million people affected by depression, 60 million people are affected by bipolar, 21 million are affected by schizophrenia, and 47.5 million are affected by dementia. The nursing problems that arise from the medical diagnosis of schizophrenia include hallucinations. Based on data from Mental Hospitals in Indonesia, about 70% of patients undergoing treatment in inpatient wards of mental hospitals experience hallucinations nursing problems. Data from the inpatient room of the Jambi Provincial Mental Hospital in 2018 from 12 rooms the number of patients experiencing hallucinations was 4320 patients. The management of hallucinations is through the continuous application of comprehensive nursing care, accompanied by incorrect modality therapies. one of them is Group Activity Therapy. Objective: To determine the effect of Sensory Stimulation Group Activity Therapy (TAK) on changes in the level of hallucinations in hallucinating patients in the inpatient ward of the Jambi Province Mental Hospital. Research Methodology Quantitative research with a Quasi Experiment research design that uses Pre-Test and Post-Test with Control Group with drawing stimulation therapy intervention, data collection is done by interview and observation. The statistical test in this study used the Independent T Test